Tópicos de álgebra linear e aplicações em problemas de economia e de engenharia - Cruvinel, Frederico Borges (2013)
This work shows the importance of the Linear Algebra and in particular of the theory of Matrices and Linear Systems to solve practical problems in various areas. We show examples of Applications of Linear Systems in closed and open models of Leontief in Economics, in closed circuits (Law Kirccho ) and in projects of construction of steel structures.